Proteomic Analysis of the Vitreous following Experimental Retinal Detachment in Rabbits - Nakul Mandal; Geoffrey P. Lewis; Steven K. Fisher; Steffen Heegaard; Jan U. Prause; Morten la Cour; Henrik Vorum; Bent Honoré (Journal of Ophthalmology)
Purpose. The pathogenesis of rhegmatogenous retinal detachment (RRD) remains incompletely understood, with no clinically effective treatment for potentially severe complications such as photoreceptor cell death and proliferative vitreoretinopathy. Here we investigate the protein profile of the vitreous following experimental retinal detachment using a comparative proteomic based approach. Materials and Methods. Retinal detachment was created in the right eyes of six New Zealand red pigmented rabbits. Sham surgery was undertaken in five other rabbits that were used as controls. After seven days the eyes were enucleated and the vitreous was removed. The vitreous samples were evaluated with two-dimensional polyacrylamide gel electrophoresis and the differentially expressed proteins were identified with tandem mass spectrometry. Results. Ten protein spots were found to be at least twofold differentially expressed when comparing the vitreous samples of the sham and retinal detachment surgery groups. Protein spots that were upregulated in the vitreous following retinal detachment were identified as albumin fragments, and those downregulated were found to be peroxiredoxin 2, collagen-Iα1 fragment, and α-1-antiproteinase F. Conclusions. Proteomic investigation of the rabbit vitreous has identified a set of proteins that help further our understanding of the pathogenesis of rhegmatogenous retinal detachment and its complications.